2015
DOI: 10.1186/s13104-015-1737-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication among medical and pharmacy students in Bangladesh

Abstract: BackgroundThis cross-sectional survey examined the pattern of self-medication and factors associated with this practice among medical and pharmacy students in context to Bangladesh.MethodsThe study used a self-administered questionnaire. A total of 500; 250 medical and 250 pharmacy, students participated in the study. As it is a comparative analysis between the medical and pharmacy students, we used independent t test and Chi square test.ResultsThe findings indicated that the impact of self-medication is almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
68
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 15 publications
13
68
1
6
Order By: Relevance
“…1 SM is reported worldwide especially in developing countries where people treat most episodes of illness by self-medication. [2][3][4] Among European countries reported SM prevalence is 21% in Lithuania, 19.8% in Romania, 15.2% in Spain, 21% in Portugal, and 31% in Czech Republic. [5][6][7] In developing countries much higher prevalence rates are reported, 79% in India, 84% in Pakistan, 78% in Saudi Arabia, 67% in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…1 SM is reported worldwide especially in developing countries where people treat most episodes of illness by self-medication. [2][3][4] Among European countries reported SM prevalence is 21% in Lithuania, 19.8% in Romania, 15.2% in Spain, 21% in Portugal, and 31% in Czech Republic. [5][6][7] In developing countries much higher prevalence rates are reported, 79% in India, 84% in Pakistan, 78% in Saudi Arabia, 67% in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the prevalence of self-medication among medical students was 81.4%. A Bangladeshi study [13] among medical and pharmacy students found all participating medical students practice self-medication. A recent study among university students in Bangladesh found 87.5% honors students self-medicated.…”
Section: Discussionmentioning
confidence: 99%
“…Main source of obtaining medications is from pharmacy (73.5%) which is accordance with a study (65.2%). [13] This is due to easy access of all medications, without prescriptions from the pharmacies and absence of strict monitoring of regulatory policies about prescriptions and over the counter sale of medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that there is high prevalence of self-medication in these areas. [2][3][4] Not only the adults do take the medicines on their own there is evidence that there is increasing incidence of self-medication to their children also. 5 However there is paucity of published data about the prevalence, causes of administration, and place of procurement of medicines for self-medication by parents to children in this region.…”
Section: Introductionmentioning
confidence: 99%